Factors Affecting on Sleeplessness of Patients in Intensive Care Unit (ICU): Sleeplessness of Patients in ICU - William, Jennifer; Sarwar, Nisha; Saddique, Humaira; Kauser , Syeda Tasneem; Ullah , Kalim (Pakistan Journal of Health Sciences, 2023)
Sleeplessness is the second problematic issue during the stay in ICU. after being discharged from hospital. Almost 51% of ICU patients complaint that their sleep habit is badly affected. Objective: To assess the factors affecting on sleeplessness of patients in intensive care unit ICU. Methods: A descriptive cross sectional research study design was conducted to examine the factors affecting on sleeplessness of patients in ICU. The population was targeted through purposive sampling techniques. Data collected from those patients who were not in very critical condition who are awaken and those who are recently shifted from ICU to ward as they were critical in ICU were targeted in this study. The targeted population was 137 of ICU patients. Data analysis were done through statistical package for the social sciences (SPSS) version-21. Results: The overall result of this study is shown that noise and light have effect on the sleep of patients. The patients who cannot sleep when lights on were 57(47.1%), the patients who disturbed by noise were 55 (40.1%). Patients who are admitted more than 3 days or a week are more disturbed by light and noise of ICU. Conclusions: Study shows that noise and light levels in ICU are above than recommended levels. So, the hospital should take steps to improve the strategies which lead to comfort of patients sleep. Noise and light play vital role in patient healing. So, they can have peaceful sleep. Study shows that these factors should be minimized by using strategies that leads patients’ health towards healing and make their life long.